2010
DOI: 10.1017/s0144686x1000084x
|View full text |Cite
|
Sign up to set email alerts
|

No way out but working? Income dynamics of young retirees in Korea

Abstract: Older people in Korea have a higher risk of poverty than younger adults, but the dynamics of income changes around the time of retirement have received little attention. This paper attempts to fill this gap by examining changes in the level and sources of income around the time of retirement, with retirement being defined as separation from one's main lifetime employment. It uses longitudinal data from the Korean Labour and Income Panel Study's Waves 1–9, and follows 580 younger retirees aged at least 50 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, these values are not reflected the greater emphasis on activities for oneself rather than for others among Koreans in our sample. Their significantly higher reporting of psychological distress is consistent with other research showing stresses on older Koreans from lack of a pension system, diminished family support, and shifts away from traditional filial piety (Bell, 2004;Harlan, 2014;Yang, 2011).…”
Section: Meaning Of Life and Psychological Distresssupporting
confidence: 87%
“…Interestingly, these values are not reflected the greater emphasis on activities for oneself rather than for others among Koreans in our sample. Their significantly higher reporting of psychological distress is consistent with other research showing stresses on older Koreans from lack of a pension system, diminished family support, and shifts away from traditional filial piety (Bell, 2004;Harlan, 2014;Yang, 2011).…”
Section: Meaning Of Life and Psychological Distresssupporting
confidence: 87%
“…It is often assumed that sharing a household with children is advantageous for elders, since various types of support and transfers tend to occur naturally and unacknowledged (Arber 2013; Thang 2010). Indeed, various studies identified important benefits from co-residence, including better mental health (Silverstein, Cong and Li 2006), a lower risk of poverty (Yang 2010) and more help from children (Song, Li and Feldman 2012). There is a widespread concern in China and other Asian countries that declining co-residence rates reflect the weakening of inter-generational ties and threaten the informal support network of older people ( see e.g.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…This is in contrast to a previous meta-analysis conducted by Murphy and Athanasou targeting Western participants, which concluded that job loss was associated with an increase in depressive symptoms and that re-employment was also related to a reduction in distress (Murphy and Athanasou 1999). The differences may result because this analysed study only targeted individuals aged 45 or above, with older workers being known to face further difficulties in discovering high-quality jobs and being more likely to find re-employment in jobs with poorer working conditions (Yang 2011). Paul and Moser's meta-analysis also demonstrated the negative mental health effects of unemployment and presented that a higher proportion of unemployed individuals show psychological problems (Paul and Moser 2009).…”
Section: Discussionmentioning
confidence: 99%